Circuit theory and interest: A simple descriptive methodology for the allocation of debt - Jan Kampen (Economic and Environmental Studies (E&ES), 2012)
A simple descriptive circuit theory of money is proposed, allowing for four actors (banks, government, firms and workers) and interest. A number of conclusions is readily made on the basis of the model. First, in an economy without a government sector (no taxes, no subsidies) and without banks granting household credit, firms end up with debt whenever they must pay interest over their loans; and when people in addition make savings, the debt situation for firms deteriorates. Second, in an economy with a government sector but without banks granting household credit, either the firms, the government, the people, or all end up with debt whenever interests on credit are positive. It is concluded that a way out of the monetary crisis without harming society at large would be the partial or total destruction of obligations on interest.
Keywords: 330; circuit theory; debt; interest; quantitative easing